European Perspectives for Public Administration The Way Forward - Bouckaert, Geert; Jann, Werner (Leuven University Press, 2020)
Strategies and priorities for the public sector in EuropeThe public sector in our society has over the past two decades undergone substantial changes, as has the academic field studying Public Administration (PA). In the next twenty years major shifts are further expected to occur in the way futures are anticipated and different cultures are integrated. Practice will be handled in a relevant way, and more disciplines will be engaging in the field of Public Administration.The prominent scholars contributing to this book put forward research strategies and focus on priorities in the field of Public Administration. The volume will also give guidance on how to redesign teaching programmes in the field. This book will provide useful insights to compare and contrast European PA with PA in Europe, and with developments in other parts of the world.Contributors: Geert Bouckaert (KU Leuven), Werner Jann (University of Potsdam), Jana Bertels (University of Potsdam), Paul Joyce (University of Birmingham), Meelis Kitsing (Estonian Business School, Tallinn), Thurid Hustedt (Hertie School of Governance, Berlin), Tiina Randma-Liiv (Tallinn University of Technology), Martin Burgi (Ludwig Maximilians University of Munich), Philippe Bezès (Science Po Paris; CNRS), Salvador Parrado (Spanish Distance Learning University (UNED), Madrid), Mark Bovens (Utrecht University; WRR), Roel Jennissen (WRR), Godfried Engbersen (Erasmus University Rotterdam), Meike Bokhorst (WRR), Bogdana Neamtu (Babes Bolyai University, Cluj-Napoca), Christopher Pollitt (KU Leuven), Edoardo Ongaro (Open University UK, Milton Keynes), Raffaella Saporito (Bocconi University, Milan), Per Laegreid (University of Bergen), Philip Marcel Karré (Erasmus University Rotterdam), Thomas Schillemans (Utrecht University), Martijn Van de Steen (Nederlandse School voor Openbaar Bestuur), Zeger van de Wal (National University of Singapore), Michael Bauer (University of Speyer), Stefan Becker (University of Speyer), Jean-Michel Eymeri-Douzans (Université de Toulouse), Filipe Teles (University of Aveiro), Denita Cepiku (Tor Vergata University of Rome), Marco Meneguzzo (Tor Vergata University of Rome), Külli Sarapuu (Tallinn University of Technology), Leno Saarniit (Tallinn University of Technology), Gyorgy Hajnal (Corvinus University of Budapest; Centre for Social Research of the Hungarian Academy of Sciences).